Characterization of eutectic systems constituted by ionic liquids - Santos, Ricardo Jorge Botas Neves dos (2018)
The main aim of this work was the study of the solid-liquid equilibrium of binary mixtures composed of ionic liquids. The ionic liquids evaluated were constituted by a common anion, the hexaflourophosphate and different nature cations as the aromatic, imidazolium, pyridinium, non-aromatic as the pyrrolidinium and piperidinium and the tetrabutylammonium and tetrabutylphosponium cations. The melting temperatures of the pure components and their mixtures were obtained by a polarized optical microscope coupled to a controlled temperature stage. Furthermore, Differential Scanning Calorimetry (DSC) was used to obtain additional information. Through the evaluation of the phase diagrams behavior, it was found that all mixtures presented an eutectic-like behavior with the exception of one system. It was found also that in most of the studied examples the eutectic behavior could be well described considering the liquid and solid phases as ideal. For some pure compounds important solid-solid transitions were observed. In the cases of the mixtures formed by these components the contribution terms based on these transitions could not be neglected when modeling the phase behavior. The similarities between mixed components justify the ideal behavior observed for most systems. Reasonable temperatures differences between the eutectic composition and the pure component were found, and in some cases over 100 K, meaning that it is possible to generate new ionic liquids from ionic solids. Some of the studied systems revealed a mild non-ideal behavior. The structural differences between components composed of different alkyl chain lengths and the aliphatic and symmetrical nature versus aromatic and asymmetrical components are the main reasons behind the deviations to the ideal behavior. The non-ideality of the liquid phase was modeled by the Margules equation. The COSMO-RS (Conductor-like Screening MOdel for Real Solvents), a model based on the combination of quantum chemistry calculations with statistical thermodynamics, was used to calculate the activity coefficients of the studied systems. A comparison was made between the values calculated by the model and experimental data. The solid-liquid phase diagrams of some systems were also calculated by COSMO-RS. The results obtained by the model were consistent with experimental data, especially for the systems with higher deviation from ideality, validating thus the ability of this model to describe the phase behavior of new systems. The system, composed of 1-propyl-3-methylpiperidinium and 1-propyl-3-methylpyrrrolidium hexafluorophosphate, presented a unique behaviour, a continuous solid solution with a formation of an alloy.